2007
DOI: 10.3892/ijo.31.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel murine anti-CD20 monoclonal antibodies and their comparison to 2B8 and c2B8 (rituximab)

Abstract: Abstract.Rituximab is the first anti-cancer antibody approved by the FDA for the treatment of B-cell non-Hodgkin lymphoma (B-NHL), alone or in combination with chemotherapeutic drugs. Further, rituximab is now being examined in a variety of CD20 + neoplastic diseases as well as B-cell-induced autoimmune diseases. The clinical response to rituximab is significant, resulting not only in tumor regression but also prolongation of survival. However, a subset of patients does not initially respond to rituximab or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…In all other cases of murine-derived mAbs, the heavy chain V region genes were derived from the VH1 family genes (13,28). These include 2B8, 2H7, 1F5, A20, B1 and B-Ly1 and most of other cases of the light chain V region genes were from Vκ4/5 family genes except for B-Ly1 which was Vκ24/25.…”
Section: Discussionmentioning
confidence: 99%
“…In all other cases of murine-derived mAbs, the heavy chain V region genes were derived from the VH1 family genes (13,28). These include 2B8, 2H7, 1F5, A20, B1 and B-Ly1 and most of other cases of the light chain V region genes were from Vκ4/5 family genes except for B-Ly1 which was Vκ24/25.…”
Section: Discussionmentioning
confidence: 99%
“…hOUBM3 and hOUBM6 are humanized versions of the murine antibodies 1k1782 and 1k1791 that were previously identified as having properties and epitope specificities different from rituximab and ibritumomab. 83 In preclinical studies, variants of hOUBM6 showed higher CDC levels, similar or higher ADCC levels and similar depletion of leukemia and lymphoma cells compared with rituximab. 75 Residues A170 and P172 of CD20 are not essential for binding of hOUBM3 and hOUBM6, suggesting that the epitope for these antibodies indeed differs from that of rituximab.…”
Section: Type II Cd20 Antibodiesmentioning
confidence: 99%
“…Recent work with TNFR agonistic antibodies including CD40 and DR5 antibodies has shown that binding to CD40 and FcγRIIb in cis is required to mediate potent CD40 or DR5 activation. [83][84][85] We propose that Type I CD20 antibodies bind to CD20 on B cells in a conformation that allows simultaneous binding to FcγRIIb on the same cell (in cis) resulting in crosslinking, FcγRIIb co-activation and CD20 co-internalization upon binding potentially in lipid rafts. Vice versa, the biological effects could be explained by the different binding conformation of Type II CD20 antibodies that might prevent simultaneous binding in cis to FcγRIIB, which precludes FcγRIIb crosslinking and CD20 co-internalization (Fig.…”
Section: Type II Cd20 Antibodiesmentioning
confidence: 99%
“…the IL-15N72D⅐IL-15R␣SuFc complex) could also function as a protein scaffold to create multispecific IL-15-based targeted immunotherapeutic agents. To test this, we converted the variable regions of the heavy and light chains of rituximab into an scFv (sc2B8) (9) and genetically fused sc2B8 to the N termini of IL-15N72D and IL-15R␣SuFc proteins of ALT-803. Based on the high binding affinity between the IL-15N72D and IL-15R␣Su domains, we expected the fusion proteins to form a heterodimeric complex between sc2B8-IL-15N72D and sc2B8-IL-15R␣SuFc.…”
Section: Creation Of Multifunctional Protein Complexes Using the Il-1mentioning
confidence: 99%